Removal of Hexavalent Chromium from Aqueous Solutions Using Azolla Plant Leaf - Mojtaba Afsharnia (Journal of Global Pharma Technology, 2017)
Soluble hexavalent chromium Cr is one of the most important and most dangerous toxic and carcinogenic heavy metals. This metal in accordance with health organizations has been classified as one of six probably carcinogenic agents through ingestion. This study was conducted to evaluate the level of removal of hexavalent chromium from aqueous solutions using Azolla plant leaf. In this experimental study, the effect of influencing variables was analyzed, including pH (2, 3, 5, 7, 8, 10 and 12), contact time (5 to 120 minutes), adsorbent dosage (0.1, 0.3, 0.5, 0.7, 0.9, 1 and 1.5 g/l) and initial phenol concentration (10-200 mg). Adsorption isotherms were studied using Langmuir, Freundlich and Temkin isotherms. The results showed that acid- heat- modified Azolla plant leaf had greater potential for absorption of chromium in comparison with washed with distilled water or unmodified conditions, so that the absorption rate was about 53% in pH 2 with an hour contact time. Also according to the results, the absorption rate in pH 2 was greater than in pH 4. Therefore, Azolla plant leaf compared with some adsorbents investigated so far is considered as an effective, suitable and inexpensive adsorbent for removal of Cr from aqueous solutions.Keywords: Hexavalent Chromium, Adsorption, Azolla, Aqueous Solutions, Adsorbent